2023
DOI: 10.1136/svn-2022-002235
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically induced thalamus infarction impairs cognition in a mouse model

Abstract: BackgroundSmall subcortical infarcts account for up to 25% of ischaemic strokes. Thalamus is one of the subcortical structures that commonly manifest with lacunar infarcts on MRI of the brain. Studies have shown that thalamus infarction is associated with cognitive decline. However, due to the lack of proper animal models, little is known about the mechanism. We aimed to establish a focal thalamus infarction model, characterise the infarct lesion and assess functional effects.MethodsMale C57BL/6J mice were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…This was shown using the MWM test, a classic test used to assess spatial memory and learning [ 35 ]. Impairments in memory have been repeatedly shown previously in both MCAO models [ 45 , 46 , 47 ] and photothrombosis models [ 48 , 49 ], including damage to the sensorimotor cortex [ 50 ]. It is likely that the focal ischemia of the sensorimotor cortex has a range of effects on other brain regions closely associated with cognitive processes [ 51 ], which may be accompanied by, for example, systemic inflammation or retrograde neuronal degeneration.…”
Section: Discussionmentioning
confidence: 89%
“…This was shown using the MWM test, a classic test used to assess spatial memory and learning [ 35 ]. Impairments in memory have been repeatedly shown previously in both MCAO models [ 45 , 46 , 47 ] and photothrombosis models [ 48 , 49 ], including damage to the sensorimotor cortex [ 50 ]. It is likely that the focal ischemia of the sensorimotor cortex has a range of effects on other brain regions closely associated with cognitive processes [ 51 ], which may be accompanied by, for example, systemic inflammation or retrograde neuronal degeneration.…”
Section: Discussionmentioning
confidence: 89%
“…In vivo, we used the photothrombotic infarction model to advance our understanding of strokes, as the model induces a photochemical reaction in the brain that releases oxygen free radicals, ultimately leading to the interruption of blood flow as a result of platelet aggregation and alteration of the blood-brain barrier, which is consistent with stroke in humans [31]. Notably, several studies have confirmed that a PT-induced stroke can cause cognitive impairment [32][33][34]. We used two well-recognized behavioral paradigms, the NOR test and Y maze, to assess the effects of a stroke on cognitive function in mice.…”
Section: Discussionmentioning
confidence: 96%